Паралельна реалізація алгоритму Едмондса–Карпа - Погорілий, С.Д.; Гусаров, А.Д. (Видавничий дім "Академперіодика" НАН України, 2008)
Formalization of the Edmonds-Karp algorithm is made using a mathematical apparatus of modified systems of algorithmic algebras, and its sequential scheme is constructed. An approach to paralleling the sequential scheme is suggested, and, as a result, several parallel schemes are obtained. An analysis of the results of scheme modeling is performed by using process-oriented and thread-oriented paradigms.